Genomic analysis of DS-1-like human rotavirus A strains uncovers genetic relatedness of NSP4 gene with animal strains in Manhiça District, Southern Mozambique - Filomena Manjate; Eva D. João; Peter Mwangi; Percina Chirinda; Milton Mogotsi; Marcelino Garrine; Augusto Messa; Delfino Vubil; Nélio Nobela; Karen Kotloff; James P. Nataro; Tacilta Nhampossa; et al. (Scientific Reports)
Abstract Post rotavirus vaccine introduction in Mozambique (September 2015), we documented a decline in rotavirus-associated diarrhoea and genotypes changes in our diarrhoeal surveillance spanning 2008–2021. This study aimed to perform whole-genome sequencing of rotavirus strains from 2009 to 2012 (pre-vaccine) and 2017–2018 (post-vaccine). Rotavirus strains previously detected by conventional PCR as G2P[4], G2P[6], G3P[4], G8P[4], G8P[6], and G9P[6] from children with moderate-to-severe and less-severe diarrhoea and without diarrhoea (healthy community controls) were sequenced using Illumina MiSeq® platform and analysed using bioinformatics tools. All these G and P-type combinations exhibited DS-1-like constellation in the rest of the genome segments as, I2-R2-C2-M2-A2-N2-T2-E2-H2. Phylogenetic analysis revealed that strains from children with and without diarrhoea clustered together with other Mozambican and global strains. Notably, the NSP4 gene of strains G3P[4] and G8P[4] in children with diarrhoea clustered with animal strains, such as bovine and caprine, with similarity identities ranging from 89.1 to 97.0% nucleotide and 89.5-97.0% amino acids. Our findings revealed genetic similarities among rotavirus strains from children with and without diarrhoea, as well as with animal strains, reinforcing the need of implementing studies with One Health approach in our setting, to elucidate the genetic diversity of this important pathogen.